Characterization of physicochemical properties of starches from improved cassava varieties grown in Zambia - Shadrack Mubanga Chisenga; Tilahun Seyoum Workneh; Geremew Bultosa; Mark Laing (AIMS Agriculture and Food, 2019)
Cassava starches processed from six different cassava varieties (Bangweulu, Katobamputa, Mweru, Kariba, Kampolombo and Chila) were assessed for variety effect on swelling, solubility, gelatinization, pasting and gel freeze-thaw stability properties. The swelling power was investigated using dispersion methods in water while gelatinization and pasting were determined using Differential Scanning Calorimetry and Rapid Visco Analyzer, respectively. The gel freeze-thaw stability was determined by syneresis method. The starch granules size of the cassava starches were in the range 1.17–22.22 μm. The swelling power and solubility index of starches were in the range of 2.22–15.63 g/g and 1.62–71.15%, respectively. Solubility index of starches correlated positively with amylose (p < 0.0001). Swelling powers of starches showed a weak negative correlation with resistant starch content. The onset (To), peak (Tp) and conclusion (Tc) gelatinization temperatures of cassava starches were ranged from 56.33–63.00 ℃, 62.00–71.29 ℃ and 69.10–77.12 ℃, respectively and varied among cassava varieties (p < 0.05). The pasting temperatures for starches were in the range of 64.54–70.54 ℃ and weak positively correlated with amylose (r = 0.231, p < 0.001). The peak viscosity (782.3–983.5 cP), breakdown viscosity (383.8–506.8 cP) and final viscosity (462.0–569.7 cP) varied (p < 0.05) among cassava varieties and exhibited negative correlation with amylose (p < 0.05, p < 0.01, and p < 0.01, respectively). The syneresis for the freeze-thaw and five freeze-thaw cycle storage were ranged from 0.00–29.11% and 0.00–42.40%, respectively, and varied (p < 0.05) among cassava varieties. The sources of variations in physicochemical properties among the cassava varieties were due to differences in amylose, protein, lipid contents, and starch granule size distribution.